NÚCLEO DE EVENTOS DO CURSO DE EDUCAÇÃO FÍSICA: AVALIAÇÃO DOS EVENTOS NA PERSPECTIVA DOS COLABORADORES DA FIDENE - Bertollo, Mauro; Mafalda, Anelise; Flora, Jéssica P. D.; Ferreira, Henrique M. (Salão do Conhecimento, 2013)
Resumo